STUDY OD COMPABILITY OF FUNGUS Beauveria bassiana (Bals.) Vuill. WITH COMMERCIAL FORMULATIONS OF FUNGICIDES AND INSECTICIDES - RIVERA-MALO, ARMANDO (Revista Colombiana de Entomología, 1993)
The fungicides triadimefon and hexagonal caused in vitro total inhibition of germination growth of the fungus Beauveria bassiana Vuill., a pathogen of the coffee berry borer Hypot 3nemus hampei (Ferrari); cyproconazol and copper oxychloride were less toxic. Among the insecticides, fenitrothion was the most detrimental, followed by pirimiphos-metil and endosulfan, dicrotophos was slightly less inhibitory. This is the first time that a fungal chlamydospore formation in B. bassiana is the recorder.